Elimination of metoclopramid by the adsorption process (GAC) and ozone process - Oussama Khemis; Gabriel Racovițeanu; Elena Vulpașu (E3S Web of Conferences)
Existence of pharmaceutical substances in water with different concentrations in natural ecosystems it poses a danger to humans and animals. Conventional methods for water treatment have proven to be relatively ineffective in removing pharmaceutical contaminants, while the more effective process used for our research to eliminate pharmaceutical substance metoclopramid are ozone processes and adsorption process. This study investigated the reduction of a pharmaceutical substance metoclopramid during two simultaneous processes (ozone process and adsorption process) applied in a large-scale drinking water treatment pilot with two different EBCTs (3 minutes and 6 minutes), and the initial concentrations used were 1.6 mg/l, 0.8 mg/l, and 0.4 mg/l. we chose ozonation, which produces many hydroxyl radicals to decompose the pharmaceutical substance metoclopramide to eliminate it, and for the adsorption process, we chose granular activated carbon with a high capacity for adsorption.